2016
DOI: 10.3390/rs8090731
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Ground and Multi-Resolution Satellite Data for Predicting the Water Balance of a Mediterranean Two-Layer Agro-Ecosystem

Abstract: Abstract:The estimation of site water budget is important in Mediterranean areas, where it represents a crucial factor affecting the quantity and quality of traditional crop production. This is particularly the case for spatially fragmented, multi-layer agricultural ecosystems such as olive groves, which are traditional cultivations of the Mediterranean basin. The current paper aims at demonstrating the effectiveness of spatialized meteorological data and remote sensing techniques to estimate the actual evapot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The same approach was tested in an olive grove in Central Italy to estimate both transpiration and SWC [12]. In that case, the behavior of an agroecosystem characterized by two layers (i.e., herbs and olive trees) was simulated, reaching an accuracy comparable to that currently obtained for the three study sites.…”
Section: Ndvi-based Swc Simulation Approachmentioning
confidence: 87%
See 1 more Smart Citation
“…The same approach was tested in an olive grove in Central Italy to estimate both transpiration and SWC [12]. In that case, the behavior of an agroecosystem characterized by two layers (i.e., herbs and olive trees) was simulated, reaching an accuracy comparable to that currently obtained for the three study sites.…”
Section: Ndvi-based Swc Simulation Approachmentioning
confidence: 87%
“…Low spatial resolution satellite images can be also used for estimating several meteorological variables [11] (http://oiswww.eumetsat.org/IPPS/html/MSG/PRODUCTS/MPE). Finally, optical images taken by several sensors can provide information on vegetation quantity and condition, which can be integrated with ancillary data to simulate site water balance and SWC at different spatial and temporal scales [12]. The simplest methods which use remote sensing data to simulate plant water loss are based on the concept of crop coefficient (Kc).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Battista et al [137] published a paper with the aim of demonstrating how spatialized meteorological data and remote sensing techniques may allow one to estimate actual ET and the soil water content of a small plot (about 0.1 ha) of an olive orchard. As a rule, for Mediterranean areas, trees were covered by several herbaceous species.…”
Section: Et Estimationmentioning
confidence: 99%
“…The surface soil water content (SWC) constitutes a small portion of the agroecosystem, but it plays a critical role in agricultural production [1,2]. Accurate estimation of surface SWC is indispensable in ecology, hydrology, climatology, and environmental and agricultural water management [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the cost-prohibitive, labor-intensive, and time-consuming in-situ measurements and complex model predictions, remote sensing technology has demonstrated great potential for estimating and monitoring surface SWC for its timeliness and convenience at larger spatial scales [12]. For instance, studies have reported that satellite data, such as those from MODIS, Landsat, and Sentinel l/2, in the wavelengths of near-infrared, thermal infrared, and microwave, can be applied to monitor SWC at different scales [1,6,13].…”
Section: Introductionmentioning
confidence: 99%